2017
DOI: 10.1039/c7ra01786c
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a silica/titania hollow nanorod and its electroresponsive activity

Abstract: In this study, a 1D oriented hollow SiO 2 /TiO 2 (HST) rod-like material was successfully fabricated via a sequential combination of sol-gel use, TiO 2 incorporation, and a sonication-mediated etching and redeposition method. This carefully manipulated new material has numerous advantageous physical and intrinsic properties, such as increased surface area, pore volume, interfacial polarization, and dielectric properties introduced from each synthetic step. The synthesized HST rod was adopted as an electrorheol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 69 publications
(48 reference statements)
0
27
0
Order By: Relevance
“…43 Previous studies have reported that materials with large Δε and short λ exhibit better ER performances under an applied E field. 6,9 Specifically, Δε can be determined by referring to the differences between fictitious (ε 0 , f → 0) and static (ε ∞ , f → ∞) dielectric constants, thus providing information on the polarizability of materials. The determined Δε values for WSNs, W-STCSs, and W-HNPs were 1.12, 2.11, and 2.42, respectively.…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…43 Previous studies have reported that materials with large Δε and short λ exhibit better ER performances under an applied E field. 6,9 Specifically, Δε can be determined by referring to the differences between fictitious (ε 0 , f → 0) and static (ε ∞ , f → ∞) dielectric constants, thus providing information on the polarizability of materials. The determined Δε values for WSNs, W-STCSs, and W-HNPs were 1.12, 2.11, and 2.42, respectively.…”
Section: mentioning
confidence: 99%
“…The ER performance is greatly affected by the dielectric properties and dispersion stability of the materials. 6 The former relates to the polarization ability of the material and the latter to the stability of the materials in the dispersing medium. Numerous polarizable materials, including organic, inorganic, metal, carbonaceous, and polymeric ones (and their composites), have been evaluated as ER materials.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Judging from the EDS results, the ST HNPs were composed of Si, Ti, and O atoms. Notably, Si atoms remained after the etching process due to the redeposition process resulting in the SiO 2 /TiO 2 composites [7,36] . In the case of Mg‐doped ST HNPs, Mg was detected along with Si, Ti, and O over the entire surface of the particles, which indicates that ST HNPs were successfully doped with Mg and well‐distributed over the surface (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…Yoon et al. fabricated silica/titania hollow nanorods with an inner cavity to lower the density [7] . A high dielectric constant can be achieved by the following methods: increasing the active surface area of the particle, coating the particle with conducting polymer, modifying polar groups, fabricating a multilayered structure, and metal‐doping.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of geometrical morphologies on the ER characteristics has always been an important topic. Many studies have shown that rod-shaped, tubular, and fibrous ER materials usually exhibit a stronger ER effect than granular materials [61,62,63]. In addition, ER materials with a high aspect ratio can exhibit better sedimentation stability [64].…”
Section: Fabrication and Morphologiesmentioning
confidence: 99%